2021
DOI: 10.1007/s11356-021-17049-6
|View full text |Cite
|
Sign up to set email alerts
|

An analysis on the effect of coronavirus (COVID-19) pandemic movement control order (MCOS) on the solid waste generation in Peninsular Malaysia

Abstract: This study intends to deal with the environmental consequences of the COVID-19 pandemic in Malaysia, by providing a summary of the effects of COVID-19 on municipal solid waste (MSW). In this analysis, the data on domestic waste collection were collected from the Solid Waste Management and Public Cleaning Corporation (SWCorp) from 1 January 2020 to 31 December 2020 to evaluate the relative changes in MSW percentage via a waste weighing method. The data consisted of the cumulative tonnage of MSW for every local … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…(2020) discovered that MCO restricted the movement of people to curb the virus's spread. Brohan et al. (2021) found a decrease in the volume of municipal solid waste during the MCO.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…(2020) discovered that MCO restricted the movement of people to curb the virus's spread. Brohan et al. (2021) found a decrease in the volume of municipal solid waste during the MCO.…”
Section: Discussionmentioning
confidence: 92%
“…It was found that the municipal solid waste began to increase when the movement control order (MCO) reached the conditional and recovery stages (Arumugam et al. , 2021; Brohan et al. , 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, Science of the Total Environment dedicated a special issue on SARS-CoV-2 and collected 15 papers [1], [4], [5], [10], [16], [24], [25], [31]- [33], [36], [43], [63], [83], [84]. The other two journals that attracted papers connected with the first query are Resources, Conservation and Recycling [81], [82], [85], [86], [102] and Environmental Science and Pollution Research [14], [21], [27], [44], [48], each of them having five papers published. Four other journals, Waste Management and Research [8], [51], [57], Journal of Hazardous Materials [9], [11], [12], Environmental Research [23], [61], [89] and Journal of Environmental Management [53], [63], [78] published three papers each.…”
Section: Resultsmentioning
confidence: 99%